Strengths Weakness Opportunities and Threats Analysis of Aquatic Tourism in Nigeria - OLADELE, Ademuyiwa Hafiz; DIGUN-AWETO, Oghenetejiri (Journal of Environmental Management and Tourism; Vol 8 No 6 (2017): JEMT Volum VIII Issue 6(22) Fall 2017, 2018)
Nigeria is a maritime country with diverse resources of fresh, brackish and marine waters. However, these endowments have not been developed into a vibrant aquatic tourism industry. This review paper appraised the state of aquatic tourism in Nigeria using SWOT analysis. The presence of abundant water resources, job creation, and revenue generation are strong points of Nigeria’s aquatic tourism industry while extensive coastline, conservation of cultural heritage, availability of labor, and the large domestic market for tourism products are some of the prospects of aquatic tourism in the country. Conversely, some of the challenges facing the industry include social unrest and insecurity, water pollution, and corruption. Some of the low points of aquatic industry are poor infrastructural development, limited engagement of host communities, non-implementation of tourism master plan, and poverty level among Nigerians. Healthy involvement of all tourism stakeholders is necessary to ensure an all-round development of aquatic tourism in Nigeria.